(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents the biodiversity of the algal flora of some fish farms in the Fergana Valley (Boltakol, Damkol, Yermazor, fish farms of Namanganbalyk LLC) and shows that the algal flora has a somewhat unique composition. It identified 5 divisions, 11 classes, 13 orders, 29 families, 163 species and varieties (21 species, 12 variations), belonging to 60 genera of algal flora. Of these, Cyanophyta-48, Bacillariophyta-91, Euglenophyta - 7, Pyrrophyta - 2, Chlorophyta - 15 species and species were formed.